Math, asked by kambleaniket77946, 6 months ago

solve the equation by creamers rule x+y=3,y+z=5 z+x=4​

Answers

Answered by XxArmyGirlxX
1

We have the equations to solve for x, y and z such that

  • x+y=3
  • x+z=4
  • y+z=5

First we should change equation in terms of x, y and z such that

  • x+y=3 => y = -x+3
  • x+z=4 => x = -z+4
  • y+z=5 => z = -y+5

We then begin substituting each variable into each equation to obtain each value. Then,

  • x+y=3 => y = -x+3 = > -(3) + 3 => y = 0
  • x+z=4 => x = -z+4 => -(x+2) + 4 => -x + 6 => x = -x + 6 => 2x = 6 => x = 3
  • y+z=5 => z = -y+5 => -(-x+3) + 5 => x - 3 + 5 => z = x + 2 => z = (3) + 2 => z = 5
Similar questions
Math, 6 months ago